COVID-19 Management in Clinical Dental Care Part III: Patients and the Dental Office - Paulo Melo; Patricia Manarte-Monteiro; Nélio Veiga; André Brandão de Almeida; Pedro Mesquita (Elsevier, 2021)
The coronavirus 2019 (COVID-19) pandemic dramatically changed all aspects of life. In the context of clinical dental care, a significant number of new recommendations have been implemented to comply with public health policies, ensuring the safety of dental care professionals, staff, and patients and preventing further spread of the virus. This article is the third in a series of 3 on the management of COVID-19 in clinical dental care and presents a set of recommendations and standards to be implemented in the context of the COVID-19 pandemic. These include remote contact with all patients for triage and guidance before scheduling a clinical visit to know if they have COVID symptoms or are positive for COVID, if they belong to a risk group, and if there is a suggestion that aerosol-generating procedures (AGPs) will be required during their visit. It also reviews additional precautionary measures in the waiting room and reception area, where the environment is reorganised to protect patients and clinical staff, avoiding situations that could result in cross contamination. The dental office operates under a strict set of guidelines, namely, use of personal protective equipment by professionals, contact with patients, a strategy to avoid aerosol-generating procedures, as well as disinfection procedures for the dental office before, during, and after each patient visit. The implementation of these protocols to mitigate cross infection and spread of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) in the dental office will help improve safety and restore the confidence required to provide dental care to patients during the COVID-19 pandemic.